Hydrological Characteristics and Water Quality Assessment of Ci Jarian River in Bojonggaling Village, Cimandiri Sub-Watershed - Whidayanti, Ella; Mumtaz, Muhamad Fikri (PT. Pubsains Nur Cendekia, 2025)
Watersheds play a crucial role in the ecohydrological system. However, land use change has reduced the hydrological function and water quality in many rural areas. This study aims to analyze the hydrological characteristics and water quality of the Ci Jarian River. The river discharge measurement method at six locations using the velocity-area method was applied and accompanied by water quality analysis based on Total Dissolved Solids (TDS), pH, and Electrical Conductivity (EC) parameters. The Ci Jarian River has an influent-intermittent flow type with a dendritic pattern and variations in valley morphology from a V-shape in the upstream to a U-shape in the downstream. The flow rate ranges from 43-286 m3/s at all observation points. TDS and EC values ​​increase from upstream to downstream, indicating the accumulation of dissolved substances due to agricultural runoff and domestic waste. Meanwhile, the pH tends to be neutral to slightly alkaline (6.8-8.5), which is still within the category of suitable water according to the Minister of Health and WHO Regulations. This study emphasizes the importance of watershed management based on sustainable land use in rural areas.